Study on the Extraction and Purification of Total Flavone in Etirfel Preparation - Liu, Dingrui; Lin, Yuan; Huang, Shanshan; Zhang, Houli; Du, Zhi; Li, Kun; Diao, Yunpeng (Asian Journal of Chemistry, 2012)
The aim of the study was to optimize and discuss the extraction and purification of total flavone in etirfel preparation using macroporous absorption resin. Orthogonal test was adopted to optimize the purification of total flavone in etirfel preparation, with water as the solvent, using the content of total flavone in etirfel preparation as the evaluation indicator. The extraction temperature, extraction time and solvent consumption were chosen as the investigational factors to screen the optimal resin via the static experiments on the two types of macroporous absorption resin, namely using AB-8 and polyamide to investigate the adsorbtion and elution of total flavone in etirfel preparation by optimizing the extraction process parameters. The optimal extraction condition was obtained using a single 1 h extraction technology, at 50 ºC, with a extract-water ratio of 1:10. The optimal condition for purification of total flavone using 10 g polyamide resin are as follows. The adsorption was carried out at a flow rate of 0.25 mL/min, the loading solution volume was 25 mL, the diameter-height ratio was 1:3 and the eluent flow rate was 1.5 mL/min. The proprietary extraction process for the highest content of total flavone was obtained in this study through the optimization of the extraction and purification, providing a chemical basis for further pharmacological studies.